To Feast or not to Feast : les défis d’Henry V à la traduction audiovisuelle - Sanchez, Nicolas (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
In 2002, Dirk Delabastita published ‘A Great Feast of Languages’, one of the most detailed, thought-provoking and celebrated studies on multilingualism in Shakespeare’s ‘King Henry V.’ Not only did he show how demanding the play was for translators who had to render its dialects as well as its French-English scenes, but he also paved the way for further analysis, by stating in his conclusion: “Our study should also be broadened by considering (…) the various translations of its two film versions.” Indeed, ‘Henry V’ was adapted on screen by Laurence Olivier in 1944 and Kenneth Branagh in 1989. This paper will explore the challenges audiovisual translation faces to re-echo each diverging voice. While dubbing is infamous for covering and domesticating original dialogues, subtitling seeks simplification and uniformity: as such, are they really suited for polyglotism? To propose an answer in keeping with current trends in AVT, this article will mostly scrutinize the French, Italian, German and Latin American versions of the more recent film adaptation.